Performance Evaluation of Pigeon Pea (Cajanus cajan L. Millsp.) Variety for Registration in the Lowland Areas of Ethiopia - Tariku Simion; Dembele Ersulo; Asnake Fikre (Advances in Agriculture)
There were few released pigeon pea varieties in Ethiopia. This study was primarily conducted to diversify the availability of varieties, thus addressing socioeconomic cross-cutting issues. From eight pigeon pea genotypes after continuous evaluation, one variety, including the local check, was promoted with the objectives of evaluating the agronomic performance and registering a new variety in lowland areas of Ethiopia. The study was carried out during the main rain seasons of 2018-2019 to enhance pigeon pea productivity in the study area. A plot size of 10 meters by 10 meters was used in six locations. The spacing between rows and plants was 1.2 and 0.5 meters, respectively. Accordingly to the simple descriptive statistics, there were variabilities in the studied traits among the tested pigeon pea genotypes. The yield advantage of 39% was recorded for the test variety, Ashenafi (ICEAP00554), over the local check, which gave an opportunity to select the best-adapted material for the test and similar agroecologies. From the current study, an average yield of 1.83 t/ha was recorded across locations for a candidate variety, Ashenafi (ICP00554). The grain yield of the local cultivar had a mean of 1.04 t/ha. As a variety, Ashenafi (ICP00554) took the shortest duration to 75% flowering and 90% maturity (115 days and 171 days), respectively. In contrast, the local cultivar (Humbo local) took a long duration to 75% flowering and 90% maturity (164 days and 221 days), respectively. As a variety, Ashenafi (ICP00554) had superior performance over the local cultivar in terms of grain yield and earliness for flowering and maturity. Based on the overall performance, Ashenafi (ICP00554) was selected and registered. Therefore, this variety is recommended to popularize and thereby enhance pigeon pea production.